Rancang Bangun Mesin Filter Oli Bekas Berbasis Arduino - Yosrhil; Fausi Lewa, Patrio; Lewi, Lewi; Hamzah, Firman (Jurnal Teknik Mesin Sinergi, 2026)
The increasing use of lubricating oil in Indonesia has resulted in a significant amount of used oil waste, which is classified as hazardous and toxic material (B3). One liter of used oil can contaminate millions of liters of groundwater and reduce soil fertility, with an estimated waste volume of around 520 million liters per year. This research aims to design a used oil filter machine based on Arduino as a solution for reusing waste oil. The system employs an Arduino Uno integrated with temperature, pressure, level (ultrasonic and float), and flow rate sensors to monitor the filtration process in real time, along with LED indicators for pump and pressure status. Test results show that the filter is capable of reducing viscosity, removing particles, and improving the color of used oil, thereby enhancing its quality and feasibility for recycling and reuse, although additional substances are still required for broader applications.